NIKAH SIRRI; PRESPEKTIF HUKUM ISLAM DAN HUKUM PERKAWINAN NASIONAL - Masturiyah, Masturiyah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
In Indonesian society, marriage has legal dualism. Namely, marriage (which) should be listed in the Religious Affairs Office (KUA) and the marriages were not recorded (Sirri marriage). In fact, if we examine more seriously, many Sirri marriages cause harm especially, on the part of women and children. And in fact, not the least negative effects caused by Sirri marriage. This paper discusses sirri marriage in the perspective of Islamic law and the National Marriage Law. Because sirri marriage not stated explicitly in both the Qur’an and hadith, hence, to determine the law (istinbat al-hukmi), jurists of Islamic law (in this case) do ijtihad whereby sirri marriage is categorized as al maslahat al murasalah, which refers to the maqasid al-shari’ah. However, sirri marriage is actually problematic for several reasons. First, sirri marriage is not part of prophetic tradition. Because, the Prophet advocates and implements wedding party (walimah al-’Ursy) with aim to proclaim marriage to the public (i’lanun nikah). On the other hand, the recording of the marriage is the leader commands (Ulil Amri). Meanwhile, Allah and the Prophet ordered to obey the leader (Amri Ulil). Since the recording of the marriage will benefit Muslims (maslahah), then Muslims should stay away from harm (mudharat). Second, sirri marriage is not in accordance with the national law of marriage, because the point ‘marriage record’ does not exist in the concept of sirri marriage. Whereas, marriage registration set forth in Article 2, paragraph 2 of Law marriage, no. 1 of 1974 and article 2, paragraph 1, 2, 3 of Law no. 9 of 1975, the Code of Civil Law (KUHP) and the Compilation of Islamic Law (KHI).